Danish Evidence of Auditors' Level of Moral Reasoning and Predisposition to Provide Fair Judgements - Warming-Rasmussen, Bent (Journal of business ethics, 2003)
The community has legislatively conferred on external auditors a special but lucrative responsibility to provide fair and independent opinions about management's preparation of company financial statements. In return, auditors are obliged by professional standards to act with integrity, independently and in the public interest. This study examined 174 auditors' predisposition to provide just and fair judgements, using Kohlberg's theory of developmental moral reasoning, one of the most widely accepted theories in justice psychology. Respondents came from five international audit firms in Copenhagen. Results indicated that auditors with pre-conventional or low level of just reasoning or comprised 64 respondents, the largest group in the sample. The pre-conventional level suggests that people will act in their own self-interest and do the right only to avoid punishment. Pre-conventional auditors have the ability to "do deals", advantageous for business. When faced with an ethical crisis, however, auditors as this level will tend to focus on their own needs at the expense of others. The post-conventional or mid level of just reasoning comprised 59 auditors, second largest group in the sample. This level indicates that these auditors have the predisposition to act fairly on principal, particularly when faced with an ethical crisis. The conventional level or mid-just reasoning consisted of 51 auditors. People with a conventional level of just reasoning believe in law and order, the maintenance of the status quo, however they tend not to be critical of laws, nor authority even if those laws and authority are unjust or evil.